A novel coating material that uses nano-sized SiO2 particles to intensify hydrophobicity and corrosion protection properties. (1st December 2016) - Ammar, Sh.; Ramesh, K.; Vengadaesvaran, B.; Ramesh, S.; Arof, A.K.
Highlights: Hybrid SiO2 nanocomposite coatings were fabricated on mild steel. Highest coating resistance were exhibited by coatings with 3 wt.% SiO2 nanoparticles. Long-term stability measurement, together with hydrophobic surface measurements, were obtained. Abstract: The influence of SiO2 nanoparticles on hydrophobicity and the corrosion protection capabilities of hybrid acrylic-silicone polymeric matrix have been investigated. Contact angle measurements (CA), atomic force microscopy (AFM), field emission scanning electron microscopy (FE-SEM), and energy dispersive X-ray spectroscopy (EDX) were used to study the hydrophobicity, morphology, and topography of the coatings. In addition, electrochemical impedance spectroscopy (EIS) and salt spray techniques were employed to evaluate the corrosion protection performance. A coating with 3 wt.% SiO2, AS 3, demonstrates significant improvement in corrosion resistance with the highest measured CA of 97.3°. Morphology and topography studies clarify the influence of nano-sized SiO2 fillers on the surface topography and demonstrated the uniform and good distribution of the embedded SiO2 nanoparticles within the polymeric matrix.